A Self‐Assembled Unit Comprising 12 Squaraine Dyes Built Up from Two Star‐Shaped Hexasquarainyl‐Benzene Molecules. Issue 11 (28th January 2019) - Schreck, Maximilian H.; Röhr, Merle I. S.; Clark, Timothy; Stepanenko, Vladimir; Würthner, Frank; Lambert, Christoph
Abstract: We describe the aggregate formation and optical properties of a star‐shaped hexaarylbenzene with six squaraine chromophores (=hexasquarainyl benzene). Comprehensive concentration‐dependence studies in acetone/CHCl3 mixtures reveal a strong propensity to form discrete dimeric aggregates with a high binding constant in excess of 10 6 m −1 . In this context, a large hypsochromic shift of almost 2700 cm −1 was found in the absorption spectrum, indicating H‐type exciton coupling. The aggregate band is characterised by a very small band width of only 560 cm −1, probably caused by exchange narrowing. Both experimental and computational methods were used to elucidate the supramolecular aggregate structure, which is assumed to consist of two stacked hexasquarainyl benzene monomers. Abstract : Concentration matters : Solvent‐ and concentration‐dependent self‐assembly of star‐shaped hexasquarainyl benzenes in well‐defined dimeric H‐type aggregates is described.